Revising the computer programming attitude scale in the context of attitude ambivalence. - Yusuf, Abdullahi; Noor, Norah Md (Journal of Computer Assisted Learning, 2023)
Background: Several attitude scales have been developed to measure students' attitudes toward computer programming, including the prominent one developed by Cetin and Ozden. The development of these scales stemmed from the elusive nature of attitude and the lack of specific constructs to measure attitude. These instruments measure students' attitudes based on one‐dimensional perspective, thus, making it difficult to interpret the meaning of some attitude evaluations such as the meaning of neutral points in a 10‐point scale (for example). Objectives: The computer programming attitude scale was modified to measure ambivalence. The study also investigate attitude differences across demographic variables and used these variables to predict ambivalence. Methods: The study was conducted in two phases. In the first phase, the instrument was validated using exploratory factor analysis and confirmatory factor analysis. In the second phase, the revised scale was administered to another 547 students in four research universities for empirical investigation. Results: Results show that the instrument is valid and suitable for measuring students' programming attitudes. Participants' attitudes skewed toward the negative attitude dimension. Lastly, we found that both attitude and ambivalence are factors of programming experience. Conclusions: We discussed the findings, recommend the instrument to programming tutors, and strongly emphasise the evaluation of students' ambivalent attitudes. Lay Description: What is currently known: There are numerous scales developed to measure students' attitude toward computer programming, such as the computer programming attitude scale (CPAS).The development of these inventories stemmed from the elusive nature of attitude and the lack of specific construct to measure attitude.These instruments measure students' attitude based on one dimensional perspective, thus, making it difficult to interpret the meaning of some attitude evaluations such as the meaning of neutral points in a 10‐point scale (for example). What this paper adds: The present research brings a novel approach to instrument development by acknowledging the presence of attitude toward computer programming.This novel approach advances the knowledge of instrument development in the field of attitude measurement by introducing a paradigm shift from conventional attitude evaluation to a more diverse approach.The study has introduced new items to the existing CPAS, and subsequently, indicates the possibility of validating an attitude inventory using data obtained from ambivalence evaluation.By using this instrument, students' attitude is measured accurately rather than adopting the conventional measures that ignored the presence of negative and positive evaluations. Implication to practitioners: Through the findings of the study, computer science and programming educators would come to know that many positive and negative attitude elements are occasionally subsumed toward an attitude object, thereby leading to an ambivalence attitude.The instrument can be used by the practitioners to accurately measure students' positive and negative attitude toward programming across all levels of education.Using the instrument, practitioners can predict the identified attitude using wide range of variables such as gender, age, computational thinking skills, programming proficiency levels, among others.